Bioaktivitas Ekstrak Etanol Biji Pinang (Arecha catechu L.) terhadap Staphylococcus aureus dan Escherichia coli: Bioactivity of Betel Nut (Arecha catechu L.) Ethanol Extract against Staphylococcus aureus and Escherichia coli - Asrianto Asrianto; Asrori Asrori; Indra Taufik Sahli; Risda Hartati; Fajar Bakti Kurniawan; Rina Purwati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Areca nut (Areca catechu Linn) is a plant that is widely distributed in tropical and subtropical regions. People have used it to treat various health problems. This study aims to determine the ability of betel nut ethanol extract to inhibit the growth of Staphylococcus aureus and Escherichia coli bacteria. The research method is experimental. Stages of research, first the betel nut is dried by aerating for 7-10 days. After drying, the seeds are ground into powder. The extraction stage of the active compounds uses the maceration method using 92% ethanol, evaporation is carried out using a rotary vacuum evaporator. The results of the maceration extract were carried out with phytochemical tests and bacterial inhibitory tests against E. coli, and S. aureus, carried out by the Kirby Bauer method. The detected metabolites were flavonoids, tannins and terpenoids. These metabolites have the ability as antimicrobials. The results of the inhibition test of the ethanol extract of areca nut seeds showed descriptively that the ethanol extract had a better inhibitory ability against S. aureus bacteria, compared to E. coli. The conclusion of this study is that the ethanol extract of areca nut seeds can inhibit the growth of E.coli and S.aureus.